Impacts of intervals between sequential development of depression and dementia in older adults: A nationwide population-based study. (July 2022) - Yang, Szu-Nian; Chueh, Chen-Han; Peng, Li-Ning; Tsai, Yi-Wen
Highlights: Approximately 20% of older people with dementia (PwD) experienced depression before the diagnosis of dementia PwD with depression (either early or recent dementia onset) increased subsequent inpatient health care utilization related to mental illness PwD with early depression are of greater risk for depression and nondepression mood disorder than other types Abstract: Background: Depression has been reported as a risk factor for dementia, as well as the continuation of dementia development. This study aimed to stratify older people with dementia (PwD) into three groups (no depression, early depression and recent depression) to compare their inpatient health care utilization and to explore related clinical impacts. Methods: Overall, 11, 612 PwD were identified from Taiwan's National Health Insurance Research Database and were further divided into 9, 257 PwD without depression, 1, 179 PwD with recent depression (< 2 years from dementia diagnosis), and 1, 176 PwD with early depression (> 2 years from dementia diagnosis). Three matched cohort pairs (Cohort 1: no depression versus recent depression, Cohort 2: no depression versus early depression, and Cohort 3: recent depression versus early depression) were constructed to compare inpatient health care utilization three years after dementia onset. Results: The incidence of hospitalization related to mental illness among PwD with a recent or early depression onset were significantly higher than their matched cohort without depression. The recent depression group had a greater rate ratio (RR) with a longer length of stay due to depression (RR: 8.29, 95% CI: 2.74-25.12) compared to the no depression group, and the early depression group had 4.24 times (95% CI: 1.56-11.59) and 6.40 times (95% CI: 2.18-18.82) longer length of stay than the no depression group due to depression, and mood disorders. Conclusions: Depression significantly increased inpatient health care utilization of depression and mood disorder among older PwD with early depression.